Report Card Grades on the Physical Activity of Children and Youth Comparing 30 Very High Human Development Index Countries - Lowri Edwards (Journal of Physical Activity and Health, 2018)
Background: To better understand the childhood physical inactivity crisis, Report Cards on physical activity of children and youth were prepared concurrently in 30 very high Human Development Index countries. The aim of this article was to present, describe, and compare the findings from these Report Cards. Methods: The Report Cards were developed using a harmonized process for data gathering, assessing, and assigning grades to 10 common physical activity indicators. Descriptive statistics were calculated after converting letter grades to interval variables, and correlational analyses between the 10 common indicators were performed using Spearman’s rank correlation coefficients. Results: A matrix of 300 grades was obtained with substantial variations within and between countries. Low grades were observed for behavioral indicators, and higher grades were observed for sources of influence indicators, indicating a disconnect between supports and desired behaviors.Conclusion: This analysis summarizes the level and context of the physical activity of children and youth among very high Human Development Index countries, and provides additional evidence that the situation regarding physical activity in children and youth is very concerning. Unless a major shift to a more active lifestyle happens soon, a high rate of noncommunicable diseases can be anticipated when this generation of children reaches adulthood.